Pengetahuan Sikap dan Perilaku Anak Remaja Usia 15-18 Tahun terhadap Penggunaan Sunscreen di SMK Kesehatan Yannas Husada Bangkalan - Safinatul Hujjah; Selma Siahaan (Jurnal Health Sains, 2022)
UV rays can have a negative impact on human skin if exposed for too long (BPOM, 2009). The lack of knowledge and the low level of use of sunscreen in adolescents so that better and more optimal education is needed. Therefore, to get an overview of this, research is needed on Knowledge of Attitudes and Behaviors of Adolescents Aged 15-18 Years Against the Use of Sunscreen at the Yannas Husada Health Vocational School in the Bangkalan area. Data was collected by distributing questionnaires to 63 respondents. The data obtained were then performed with univariate analysis using IBM SPSS software and chi square test. The results of the univariate analysis showed that as many as (4.8%) of respondents had a good level of knowledge, (47.6%) had a fairly good knowledge and (47.6%) had a poor knowledge of the use of sunscreen. Then as many as (3.17%) respondents have a good attitude, (50.79%) have a fairly good attitude and (46.03%) have a bad attitude towards the use of sunscreen. Then (0%) respondents have good behavior, (30.2%) have quite good behavior and (69.8%) have bad behavior towards the use of sunscreen. The chi square test shows that all variables have a value of more than 0.05 so there is no relationship between them. Teenagers or students of Yannas Husada Health Vocational School have a fairly good level of knowledge, attitude and behavior towards the use of sunscreen